We have to solve:

x + y - 14 = 0 ...(1)

4x - y - 11 = 0 ...(2)

From (1)

x + y - 14 = 0

=> -y = x - 14

Substitute in (2)

4x + x - 14 - 11 = 0

=> 5x - 25 = 0

=> x = 25/5

=> x = 5

y = 14 - x

=> y = 14 - 5

=> y = 9

**The required solution is x = 5 and y = 9**

x+y-14=0

x = 14 - y

replace y

4x-y-11=0

subtract 11

4(14 - y) - y = 11

56 - 4y - y = 11

combine like terms

- 4y - y = -56 + 11

-5y = -45

divide by -5

y = 9

now plug this in as y to get x

x+9-14=0

x - 5=0

add 5

x= 5

x+y-14=0

x = 14 - y

now replace y with those numbers in any of the equations:

4x-y-11=0

subtract 11

4(14 - y) - y = 11

56 - 4y - y = 11

combine like therms

- 4y - y = -56 + 11

-5y = -45

divide by -5

**y = 9**

now plug this in as y to get x

x+9-14=0

x - 5=0

add 5

**x= 5**

We'll re-write the equations, keeping the variables x and y to the left side:

x + y = 14 (1)

4x - y = 11 (2)

We'll solve the system using substitution:

x = 14 - y (3)

We'll replace x in the 2nd equation by the expression from (3):

4(14 - y) - y = 11

We'll remove the brackets:

56 - 4y - y = 11

-5y = 11 - 56

-5y = -45

We'll divide by -5:

y = 9

We'll substitute y in (3):

x = 14 - 9

x = 5

**The solution of the system is the pair: (5 ; 9).**